Online User Information Sharing and Government Pandemic Prevention and Control Strategies-Based on Evolutionary Game Model - Xiao, Yao; Xu, Wanting; Zeng, Shouzhen; Peng, Qiao (Frontiers in Public Health, 2021)
Background: The sharing and utilization of online users’ information has become an important resource for governments to manage COVID-19; however, it also involves the risk of leakage of users’ personal information. Online users’ sharing decisions regarding personal information and the government’s COVID-19 prevention and control decisions influence each other and jointly determine the efficiency of COVID-19 control and prevention. Method: Using the evolutionary game models, this paper examines the behavioral patterns of online users and governments with regard to the sharing and disclosure of COVID-19 information for its prevention and control. Results: This paper deduce the reasons and solutions underlying the contradiction between the privacy risks faced by online users in sharing information and COVID-19 prevention and control efforts. The inconsistency between individual and collective rationality is the root cause of the inefficiency of COVID-19 prevention and control. Conclusions: The reconciliation of privacy protection with COVID-19 prevention and control efficiency can be achieved by providing guidance and incentives to modulate internet users’ behavioral expectations.